The Impact of Big Data Applications in Health Care Industry - Vanjulavalli, N; Saravanan, M (International Journal of Computer Sciences and Engineering, 2025)
With the advent of new technologies, devices and communication means like social networking sites the amount of data produced by mankind is increasing every year. Though the information produce is meaningful, it can be useful only with proper data analytics. There is a vast amount of data generated in the healthcare industry in recent years. This paper discusses about the recent research of big data tools and approaches for the analysis of healthcare informatics data gathered at various levels. The data thus collected is to be structured and analyzed for finding possible solutions. In this paper we use the predictive analysis algorithm in Hadoop and Map Reduce to predict the diabetes prevalent, complications associated with it and the type of treatment to be provided. The result is predicted based on the analysis of big data in an efficient way to cure and care the patients